1976
DOI: 10.1021/bi00669a020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the cyanogen bromide fragments of the β chain of human haptoglobin

Abstract: Characterization of the cyanogen bromide (CNBr) fragments of the beta chain of human haptoglobin revealed five major fragments resulting from cleavage of four methionyl residues. The fragments were isolated by gel filtration in guanidine-HCl on Sepharose 6B and Bio-Gel P10 and P60. Compositional analyses of the five cyanogen bromide fragments accounted for 248-253 amino acid residues in agreement with the number of residues determined for the intact beta chain. Most of the carbohydrate was attached to CNBr II.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1977
1977
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This residue is an Asp in HpH, as pointed out by Kurosky et al (6), suggesting trypsin-like specificity. The restriction of the elastase substrate specificity to small side chains is believed to be due to blockage of the hydrophobic pocket that binds the side chain of the substrate by Val C216 and Thr C226, which replace glycines found in chymotrypsin and trypsin (12).…”
Section: Properties Of the Model Hph Structure Structural Homology Ofmentioning
confidence: 60%
See 2 more Smart Citations
“…This residue is an Asp in HpH, as pointed out by Kurosky et al (6), suggesting trypsin-like specificity. The restriction of the elastase substrate specificity to small side chains is believed to be due to blockage of the hydrophobic pocket that binds the side chain of the substrate by Val C216 and Thr C226, which replace glycines found in chymotrypsin and trypsin (12).…”
Section: Properties Of the Model Hph Structure Structural Homology Ofmentioning
confidence: 60%
“…Kurosky et al (4)(5)(6) have suggested that the active-site residues of the serine proteases, Ser C195, His C57, and Asp C102, are Ala, Lys, and Asp in HpH, respectively. In addition, the Asp that precedes the reactive Ser is conserved.…”
Section: Properties Of the Model Hph Structure Structural Homology Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification and characterization of the CNBr peptides were reported by Kurosky et al (24). Purified CNBr fragments II, III, IV, and V were subjected to hydrolysis* with chymotrypsin, trypsin, staphylococcal protease, and thermolysin.…”
Section: Methodsmentioning
confidence: 99%
“…This could be due to an anomalous reaction of the expected aminoterminal tryptophan of CB3 during the digestion with cyanogen bromide. Anomalous cleavage of protein chains amino-terminal or carboxyl-terminal to tryptophan has been reported by, for example, Braunitzer and Aschauer [20] and Kurosky et al [21].…”
Section: Cyanogen Bromide Peptidesmentioning
confidence: 95%